Perception of Community Leaders on Escalation of Neo Paganism in Aguata Local Government Area of Anambra State (Journal of Guidance and Counselling Studies, 2025)
This study examined perception of community leaders on escalation of idol worship in Augata Local Government Area of Anambra State. Four research questions guided the study. Descriptive survey research design was used for the study. The population of the study comprised 1,268 community leaders who are community elders and religious leaders in the 12 towns in Aguata Local Government Area of Anambra State. The sample size consisted of 100 community leaders (65 community elders and 35 religious leaders) using the purposive sampling technique. Data for the study was collected by means of questionnaire titled “Perception of Community Leaders on Escalation of Idol Worship Questionnaire” (PCLEIWQ). The questionnaire was validated by two experts. Mean and standard deviation were used to answer the research questions. It was found that community leaders in Aguata Local Government Area of Anambra State have agreed on strategies to reduce idol worship among youths, including escalating shrine patronage, native doctors' patronage, and masquerade cult initiation. They also agreed on strategies to reduce idol worship in the area. Based on the findings, it was recommended amongst others that religious bodies should develop support networks within families, churches, and community centers that offer guidance, counseling, and mentorship to youths.
Keywords: Leaders; Community Leaders; Idol; Idol Worship; Aguata Local Government